A study of relationship between some salivary factors and dental caries of preschool children in Lattakia city - سلمان, بسام; حمامة, طارق (Latakia University Journal -Medical Sciences Series, 2021)
Objective: This study aims to determine the prevalence and severity of ECC in 3 to 5 -year children in Lattakia and the correlation of saliva pH, buffer capacity and salivary flow rate with the dental caries. Materials and methods: An epidemiological study of N = 400 children was conducted to determine the prevalence of ECC in Lattakia’s kindergartens and the association between child's gender, age and caries.The salivary tests for N = 40 children, the mean number of teeth, carious surfaces, restored and lost due to caries were measured. Results: The results indicated a high prevalence of Ecc among children (69.8%) We did not find significant differences in dmft, dmfs between children according to gender or age. The adjusted ability of saliva was high for 65% and medium for 35%. On the other hand, it was found that there is an inverse correlation between saliva pH and the studied indicators.